Current trends and future developments on (bio- ) membranes. principles, applications, advances - Basile, Angelo (Angelo Bruno); Cassano, Alfredo; Rastogi, Navin K. (Elsevier, 2019)
Current Trends and Future Developments on (Bio- ) Membranes: Reverse and Forward Osmosis: Principles, Applications, Advances covers the important aspects of RO, FO and their combination in integrated systems, along with their specific and well-established applications. The book offers an overview of recent developments in the field of forward and reverse osmosis and their applications in water desalination, wastewater treatment, power generation and food processing. General principles, membrane module developments, membrane fouling, modeling, simulation and optimization of both technologies are also covered. The book's ultimate goal is to support the scientific community, professionals and enterprises that aspire to develop new applications.